Optimization of electroless Ni-Co-P coating with hardness as response parameter: A computational approach - Subhasish Sarkar; Rishav Kumar Baranwal; Sameer Lamichaney; Jhumpa De; Gautam Majumdar (Jurnal Tribologi, 2018)
This paper reports the effects of the coating parameters on the hardness of the coating with the application of Taguchi method. The three factors viz. concentration of Cobalt sulphate, concentration of Sodium Hypophosphite and the temperature of electroless bath with three different levels each are fitted into L27 orthogonal arrays to optimize the coating conditions. The optimized results were obtained for 10 g/L concentration of Cobalt Sulphate, 25 g/L concentration of Sodium Hypophosphite and 85̊C temperature. The micro hardness of this coating was 1790 VHN10g. With the help of annealing at 400̊C the micro-hardness increased to 2027 VHN10g. Analysis of variance was applied to find the significant factors and the interactions. It has been investigated that concentration of Cobalt Sulphate and concentration of Sodium Hypophosphite were the most significant factors in determining the hardness of the Ni-Co-P coating. Presence of different phases (Co2P and Ni3P) in the coating was found using X-Ray diffraction analysis and composition of the coating was investigated using Energy-dispersive X-Ray Spectroscopy (EDAX). It showed high percentage of Cobalt (13.27%) and Phosphorus (8.85%) along with Nickel. Scanning Electron Microscopy analysis was used for observing the micro-structure of the substrate, optimized coating and annealed optimized coating.